Calculation of Mesh Stiffness for ZC3 Worm Gear and Worm based on the Finite Element Method - Chen Wei; Wang Guomin; Lin Jiajie; Zhang Zhiyong (Jixie chuandong)
The calculation of the meshing stiffness of the worm gear is the basis of the foundation of dynamics analysis. In view of the Uzbekistan Maidanak observatory 1 m telescope worm gear and worm drive renovation project,based on the theory of finite element analysis for ZC3 worm gear with loaded contact,a method for calculating the time-varying meshing stiffness of ZC3 worm gear is proposed. The finite element model is built by using Workbench and the meshing stiffness curve is obtained. The results show that the meshing curve of ZC3 worm has obvious periodicity. The minimum value of the meshing stiffness is 104. 4 MN·m,which appears at the position where the front pair of teeth exits meshing in the double tooth contact area of the teeth.And the maximum value of the meshing stiffness is 219. 7 MN·m,which appears in the middle of the single tooth contact zone. The basic conditions for the dynamics analysis of reconstruction project is provided by the research result.